(untitled) (Tunas Geografi, 2023)
This study aims to determine the potential of the Juang Rantauprapat Monument as a Historical Tourism Object in Labuhanbatu Regency. In this study, the research method used by the author is a qualitative research method and interviews. Qualitative research seeks to understand situations in natural settings; the authors try not to manipulate the observed phenomena. The author uses data collection guidelines, namely interviews. The data collection method uses "snowball sampling" because, in this method, the number of informants is not predetermined, apart from the key informants, namely Labuhanbatu senior journalists and residents who live around the location. The results of this study found that Tugu Perjuangan 45 has the potential as a historical tourist spot, a unique place, rich in nature, easy to access, and processed by human hands as well as the historical value of the struggle of the Labuhanbatu people. Civil Government, under the leadership of M Djamaluddin Tambunan. Various factors of historical heritage influence the attractiveness of historical tourism, so it is necessary to identify all the elements to be studied. Local governments and communities around historical tourism areas are like links in a chain that support each other in developing and maintaining tourist attractions. In an era where all social media live every time. Keywords: Potential, Monument of Fighting, Historical Tourism Objects